The use of palliative medications before death from prostate cancer: Swedish population-based study with a comparative overview of European data. (January 2018) - Lycken, Magdalena; Drevin, Linda; Garmo, Hans; Stattin, Pär; Adolfsson, Jan; Lissbrant, Ingela Franck; Holmberg, Lars; Bill-Axelson, Anna
Abstract: Background: Symptoms of terminal cancer have previously been reported as undertreated. The aim of this study was to assess the use of palliative medications before death from prostate cancer. Methods: This Swedish register study included men who died from 2009 to 2012 with prostate cancer as the underlying cause of death. We assessed the proportion who collected a prescription of androgen deprivation therapy, non-steroidal anti-inflammatory drugs, paracetamol, opioids, glucocorticoids, antidepressants, anxiolytics and sedative-hypnotics and the differences in treatment related to age, time since diagnosis, educational level, close relatives and comorbidities. Data were collected from 3 years before death from prostate cancer. Results: We included 8326 men. The proportion who received opioids increased from 30% to 72% during the last year of life, and 67% received a strong opioid at the time of death. Antidepressants increased from 13% to 22%, anxiolytics from 9% to 27% and sedative-hypnotics from 21% to 33%. Men without close relatives and older men had lower probability to receive opioids (odds ratio [OR]: 0.56, 95% confidence interval [CI]: 0.47–0.66 for >85 years versus <70 years) and (OR 0.78, 95% CI: 0.66–0.92 for unmarried without children versus married with children). Conclusion: Our results represent robust epidemiological data from Sweden for comparison of palliative care quality between countries. The findings indicate that men without close relatives and older men are disadvantaged with respect to the treatment of cancer pain and need closer attention from health care providers and highlight the importance to identify psychological distress in terminal prostate cancer. Highlights: Men without close relatives were found to receive less opioids. Older men were found to receive less ADT, opioids and anxiolytics. Opioids were prescribed to 72% of the men in the cohort at death. use of medications for mood disorders was found to increase in terminal disease. Low education was found to increase the probability to receive opioids.